Farmers’ Attitudes towards Participation in short Food Supply Chains: Evidence from a Chinese field research - Wang, Meng; Kumar, Vikas; Ruan, Ximing; Neutzling, Daiane Mulling (Revista Ciências Administrativas, 2019)
As the industrialized agro-food supply systems have been commonly criticized for their adverse environmental and social impact, Short food supply chains have emerged as a promising sustainable alternative. Given that the history of SFSCs is relatively short, the majority of empirical evidences is from developed countries, and existing studies on SFSCs in developing country context are rather limited. Therefore, this study aims to investigate the farmers’ attitudes towards participating in SFSCs by conducting a field research in China. Semi-structured interviews were implemented with eight participants selected from a local farmer market as a pilot study. The social and economic reasons are found to be the main motivations of Chinese farmers participating in SFSCs. However, none of these interviewed participants are aware of the environmental effects of SFSCs. Moreover, the findings were cross-compared with existing studies conducted in developed countries. It was found that Chinese farmers participating in SFSCs are mainly passive choice, as they lack of relevant knowledge and governmental support.